Oxymatrine attenuates diabetes-associated cognitive deficits in rats - Wang Suo-bin; Jia Jian-ping (Acta Pharmacologica Sinica, 2016)
Suo-bin WANG, Jian-ping JIA* Department of Neurology, Xuanwu Hospital, Capital Medical University, Beijing 100053, China Aim: Oxymatrine (OMT) is the major quinolizidine alkaloid extracted from the root of Sophora flavescens Ait (the Chinese herb Kushen) and exhibits diverse pharmacological actions. In this work we investigated the effects of OMT on diabetes-associated cognitive decline (DACD) in a rat model of diabetes and explored the mechanisms of action. Methods: Male Wistar rats were injected with streptozotocin (65 mg/kg, ip) once to induce diabetes. The rats were then treated with vehicle or OMT (60 or 120 mg/kg per day, ip) for 7 weeks. Memory function was assessed using Morris water maze test. The levels of malondialdehyde (MDA), superoxide dismutase (SOD), glutathione (GSH), NF-κB p65 unit, TNF-α, IL-1β and caspase-3 in the cerebral cortex and hippocampus were quantified. Results: The diabetic rats exhibited markedly reduced body weight and increased plasma glucose level. The memory function of the rats assessed using Morris water maze test showed significant reduction in the percentage of time spent in the target quadrant and the number of times crossing the platform, coupled with markedly prolongation of escape latency and mean path length. Moreover, the rats showed oxidative stress (significantly increased MDA, decreased SOD and reduced GSH levels), as well as significant increases of NF-κB p65 unit, TNF-α, IL-1β and caspase-3 levels in the cerebral cortex and hippocampus. Chronic treatment with OMT dose-dependently reversed these behavioral, biochemical and molecular changes in the diabetic rats. However, the swimming speed had no significant difference among the control, diabetic and OMT-treated diabetic rats. Conclusion: Chronic treatment with OMT alleviates diabetes-associated cognitive decline in rats, which is associated with oxidative stress, inflammation and apoptotic cascades. Keywords: oxymatrine; quinolizidine; diabetes; diabetes-associated cognitive decline; learning memory; oxidative stress; inflammation; apoptosis; cerebral cortex; hippocampus * To whom correspondence should be addressed. E-mail jianpingjiamr@163.com Received 2013-07-29 Accepted 2013-09-25